Accumulation and depletion of fertilizer originated nitrate-N and ammonium-N in deeper soil layers - Füleky, György (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2014)
The leaching process of nitrate was studied in a long-term field experiment at Gödöllő on a brown forest soil started in 1969. 0, 90, 180, 270, 360 kg ha-1 y-1 N doses have been broadcasted as basal fertilization in the form of ammonium-nitrate for 16 years. The test plant was maize in monoculture. In autumn 1989 fertilization was discontinued and alfalfa was sown on the experimental area. In 1995 pseudoacacia was planted into the field. In 1986, 1989, 1994 and 2003 the soils of the treatments were sampled in 6 replications from 0 to 3 meters depth at every 20 cm. The nitrate-N and ammonium-N content of the sample was determined.Increasing the dose of nitrogen fertilization nitrate content in the soil profile increased, as well. About the half of fertilizer nitrogen can be found in the 3 meter layer of the soil profile after 16 years fertilization. Using deep rooting plants the accumulated nitrogen could be used to prevent the leaching losses.Results prove the necessity of a suitable technology preventing nitrate losses. As the experiment shows 100 kg N ha-1 fertilizer nitrogen enough for the maximum crop yield in this area. The amount of nitrate-N exceeding plant demand could be leached into 1-3 meter depth of soil or into deeper horizons.
Keywords: ammonium-N; fertilizer; field experiment; nitrate-N; soil